Cultural Barriers in Implementing the Original Method of Suggestopedia in the Tefl - Fitri, Trie Eka; Setiyadi, Agustinus Bambang; Sukirlan, Muhammad (FKIP Universitas Lampung, 2024)
Cultural Barriers in Implementing the Original Method of Suggestopedia in the TEFL. Objectives: The study examines whether the previous studies conducted by Indonesian researchers applied the original Suggestopedia teaching procedure developed by Professor Lozanov or the modified ones through the implementation of two main characteristics of the original Suggestopedia in the teaching procedures which are fictitious identity and classical music. Methods: This study uses the qualitative library method which combines data taken from books, reputable indexed international journals, and articles, as the source of data reference. The collected data has been analyzed qualitatively through peer correction among the researchers regarding the topic of investigating the originality of the Suggestopedia method used by Indonesian researchers in previous studies. Findings: The results and findings show that previous research conducted by Indonesian researchers applied the modified Suggestopedia, not the original one due to the difficulties of adjusting the original Suggestopedia method to the time, curricula, and concepts of Indonesian pedagogy. Conclusion: The difficulties reflect the cultural barriers of views, beliefs, and attitudes in implementing original Suggestopedia as a set of TEFL methods in Indonesian pedagogy.Keywords: suggestopedia, indonesian pedagogy, second language acquisition, cultural barriers in TEFL.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024104